Searching for Culture in “Cultural Capital”: The Case for a Mixed Methods Approach to Production Facility Siting - Boglioli, Marc; Mueller, Daniel W.; Strauss, Sarah; Hoard, Season; Beeton, Tyler A; Budowle, Rachael (Frontiers in Energy Research, 2022)
Site-selection modeling receives much attention in the aviation biofuels literature to ensure the sustainability of the aviation biofuel supply chain. As these models seek to reflect the multitude of factors and conditions necessary for supply chain success, more attention has been paid to social factors that impact success but are often excluded due to difficulties obtaining accurate and standard measures. Some of the most promising work in this arena utilizes a “community capitals approach” to create statistically grounded decision support tools (DSTs) intended to provide a rapid assessment of the social characteristics of potential facility locations. Despite the value of the community capitals approach, this methodology is still marked by inconsistent predictivity due to an inability to reliably assess the cultural and historical nuances of local communities that are so vitally important to the long-term viability of these costly projects. This paper more fully examines the Community Assets and Attributes Models (CAAM) that has been developed and applied in the Pacific Northwest to incorporate social assets in site-selection modeling. Based on ethnographic fieldwork in Colorado and Wyoming dealing with biomass/bioenergy facility siting, we argue that key aspects of the model, cultural capital, are biased to urban locations due to the measurements incorporated and that current site-selection modeling based on the Community Capitals Framework does not accurately reflect rural region community assets. We argue, as measured, the CAAM does not actually measure cultural capital but is a product of cultural capital, creativity, and innovation, and thus should be referred to as creative capital. Our mixed-method approach that combines quantitative assessment with ethnographic research highlights the limits of these measures, as local residents showed a willingness to innovate but also referred to history with similar industries that may limit support. This work demonstrates that a mixed-methods approach combining ethnographic and historical methodologies with existing quantitative community capital approaches will produce a more effective predictive methodology for facility siting due to its heightened ability to gather critical data on place-based values, beliefs, and historical legacies relating to natural resource development in general, and the timber industry specifically.